2019
DOI: 10.1101/836346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameter tuning facilitates the evolution of diverse tunneling patterns in termites

Abstract: 9The nest structures built by social insects are complex group-level patterns that emerge from 10 interactions among individuals following simple behavioral rules. The theory of complex systems 11 predicts that there is no simple one-to-one relationship between variations in collective patterns and 12 variation in individual behaviors; therefore, it is essential to know how actual behavior evolves to 13 change pattern formation. Here we demonstrate that the evolutionary divergence of termite tunneling 14 patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These observations suggest that the common ancestor of modern termites was a multiple‐piece nester able to build shelter tubes and tunnel through soil. However, in disagreement with this hypothesis, a recent comparative study found that the behavioral rules for collective excavation of tunnels shared by Reticulitermes tibialis and Heterotermes aureus (Rhinotermitidae) are not shared by Paraneotermes simplicicornis (Kalotermitidae) (Mizumoto, Bardunias, et al, 2019), possibly indicating an independent origin of tunneling in P. simplicicornis following the secondary loss of shelter tubes in Kalotermitidae. These results indicate that the comparison of a limited set of species is insufficient to determine the evolutionary processes at the origin of tunneling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that the common ancestor of modern termites was a multiple‐piece nester able to build shelter tubes and tunnel through soil. However, in disagreement with this hypothesis, a recent comparative study found that the behavioral rules for collective excavation of tunnels shared by Reticulitermes tibialis and Heterotermes aureus (Rhinotermitidae) are not shared by Paraneotermes simplicicornis (Kalotermitidae) (Mizumoto, Bardunias, et al, 2019), possibly indicating an independent origin of tunneling in P. simplicicornis following the secondary loss of shelter tubes in Kalotermitidae. These results indicate that the comparison of a limited set of species is insufficient to determine the evolutionary processes at the origin of tunneling.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider belowground tunnels, which have the same function as shelter tubes and may experience similar evolutionary processes (Mizumoto, Bardunias, & Pratt, 2019). Yet, these two structures can be distinguished in terms of their complexity; tunneling is mainly performed by excavation and can be considered as an extension of feeding activities (Emerson, 1938), while shelter tube construction requires specific deposition patterns to form tube‐like structures.…”
Section: Evolution Of Shelter Tube Construction In Termitesmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that natural selection acts on the neural substrate that encodes the underlying behavioral rules. Across species of social insects, for example, workers may respond differently to local cues during nest construction, which could translate into different nest architectures (Mizumoto et al, 2019;Theraulaz and Bonabeau, 1995). Such behavioral rules can evolve rapidly, as has been demonstrated via artificial selection experiments on collective movement in guppies (Kotrschal et al, 2020).…”
Section: Main Textmentioning
confidence: 97%